The Right to Custody: A Study In Light of the Conflict in Comparative Arab Legislation - Kaiss Mohammed, Bashar; Hamad, Adheed Ezzat; Salih, Sawsan Safi (International Journal of Psychosocial Rehabilitation, 2020)
The issue of custody is one of the most important effects of mixed marriage between two people of different nationalities, which is represented in its first form, which is divorce, and from here the young is a subject of dispute before the judiciary, and if most comparative personal status legislation has addressed the right to custody and who are the stakeholders in that, Except this issue has raised broad problems in the field of conflict of laws, especially since most comparative legislation has been silent on defining a base of support in view of custody disputes with a foreign component, which has sparked widespread debate in jurisprudence and the judiciary about the appointment of the applicable law, and on the other hand, some legislations, including Iraq, singled out the nursery with a support rule that requires the application of the husband’s nationality law, and despite that, there remain problems related to the application of the foreign law concerned, including the timing of his choice and the accompanying cases of multiple nationality and lack thereof, not to mention the possibility of excluding him for violating the provisions of the judge’s law.